Solid electrolyte particle and preparation method thereof, diaphragm, battery and energy storage device
By using coaxial electrostatic spraying technology in the battery separator, the problem of Hipot poor caused by strong water absorption of inorganic solid electrolytes is solved, and the higher membrane preparation yield and the bonding performance of the electrolyte coating are achieved.
Patent Information
- Application Number
- CN202510112320.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The inorganic solid electrolyte in existing battery separators has strong water absorption, which leads to prone to poor Hipot during high voltage testing, affecting the preparation yield of the separator.
Solid electrolyte particles including core and adhesive layer are used. The core is an inorganic solid electrolyte, such as titanium aluminum lithium phosphate, and the adhesive layer is polyvinylidene fluoride. It is prepared by coaxial electrostatic spraying technology to ensure that the adhesive layer evenly wraps the core and improves the hydrophobicity of the particles.
The hydrophobicity of the battery separator is improved, the moisture content is reduced, and the risk of Hipot is reduced during high voltage testing is reduced, thereby improving the preparation yield of the separator and improving the bonding performance of the electrolyte coating to the electrode sheet.
Smart Images

Figure CN119560624A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and specifically to a solid electrolyte particle and a preparation method thereof, a diaphragm, a battery and an energy storage device. Background Art
[0002] In the related art, a layer of electrolyte coating containing solid electrolyte is coated on the surface of the battery's diaphragm to improve the battery's kinetic performance and energy efficiency (referred to as energy efficiency). However, the inorganic solid electrolyte in the related art has strong water absorption and high water content, which can easily cause hipot failure when the battery is subjected to a high voltage test (hipot test). Summary of the invention
[0003] In a first aspect, an embodiment of the present application provides a solid electrolyte particle, which includes a core and an adhesive layer, wherein the adhesive layer is wrapped around the surface of the core, the core includes an inorganic solid electrolyte, and the water contact angle θ of the solid electrolyte particle is in the range of 95°≤θ≤115°.
[0004] In some embodiments, the water content of the solid electrolyte particles is less than or equal to 1000 ppm.
[0005] In some embodiments, the inorganic solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum titanium oxide; and the adhesive layer includes polyvinylidene fluoride.
[0006] In some embodiments, the particle size d1 of the core is in the range of 300 nm≤d1≤700 nm.
[0007] In some embodiments, the thickness d2 of the adhesive layer is in the range of 100 nm≤d1≤400 nm.
[0008] In some embodiments, the solid electrolyte particles have an ionic conductivity ranging from 1.4 mS / cm to 2.0 mS / cm.
[0009] In a second aspect, the present application also provides a method for preparing solid electrolyte particles, the preparation method comprising: providing a core dispersion and a binder solution; and Coaxially electrostatically spraying the core dispersion and the binder solution so that the binder forms a bonding layer to obtain the solid electrolyte particles; The solid electrolyte particles include a core and an adhesive layer, the adhesive layer is wrapped around the surface of the core, the core includes an inorganic solid electrolyte, and the water contact angle θ of the solid electrolyte particles is in the range of 95°≤θ≤115°.
[0010] In a third aspect, an embodiment of the present application further provides a diaphragm, the diaphragm comprising: basement membrane; and An electrolyte coating, wherein the electrolyte coating comprises the solid electrolyte particles described in the embodiment of the first aspect of the present application.
[0011] In some embodiments, the electrolyte coating has a thickness ranging from 0.5 μm to 3 μm.
[0012] In some embodiments, the thermal shrinkage of the diaphragm after heating at 130° C. for 30 minutes is less than or equal to 5%.
[0013] In a fourth aspect, an embodiment of the present application further provides a battery, comprising: an electrolyte, a positive electrode plate, the diaphragm described in the third aspect of the present application, and a negative electrode plate, wherein the diaphragm is located between the positive electrode plate and the negative electrode plate.
[0014] In some embodiments, the electrolyte coating is located between the base film and the positive electrode plate.
[0015] In a fifth aspect, an embodiment of the present application further provides an energy storage device, comprising: The housing; and A plurality of batteries as described in the fourth aspect of the present application are housed in the box.
[0016] The solid electrolyte particles of the embodiment of the present application include a core and an adhesive layer, wherein the adhesive layer is wrapped around the surface of the core, and the core includes an inorganic solid electrolyte. When the solid electrolyte particles are applied to the battery diaphragm, the adhesive layer (such as PVDF) will be swollen by the electrolyte, and the inorganic solid electrolyte of the core can increase the migration rate of ions (such as lithium ions), thereby improving the kinetic performance and energy efficiency of the battery; in addition, the water contact angle (i.e., water drop angle) θ of the solid electrolyte particles is in the range of: 95°≤θ≤115°, so that the solid electrolyte particles have good hydrophobicity and thus have a lower water content. When applied to the battery diaphragm, Hipot failure is not likely to occur when the battery is subjected to high-voltage testing, thereby improving the preparation yield of the diaphragm; furthermore, the adhesive layer can also play a role of weak bonding with the positive electrode sheet or the negative electrode sheet, thereby improving the bonding performance of the interface between the electrolyte coating and the positive electrode sheet or the negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 It is a structural block diagram of an energy storage system according to an embodiment of the present application.
[0019] Figure 2 This is an application scenario diagram of an energy storage system according to an embodiment of the present application.
[0020] Figure 3 It is a schematic structural diagram of an energy storage device according to an embodiment of the present application.
[0021] Figure 4 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.
[0022] Figure 5 The battery of one embodiment of the present application is Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.
[0023] Figure 6 It is a schematic diagram of the structure of the positive electrode plate of one embodiment of the present application.
[0024] Figure 7 It is a schematic diagram of the structure of the negative electrode plate of one embodiment of the present application.
[0025] Figure 8 It is a schematic structural diagram of a diaphragm according to an embodiment of the present application.
[0026] Fig. 9 It is a schematic diagram of the structure of solid electrolyte particles according to an embodiment of the present application.
[0027] Fig.10 It is a schematic flow chart of a method for preparing solid electrolyte particles according to an embodiment of the present application.
[0028] Fig.11 This is a transmission electron microscope image of the solid electrolyte particles prepared in Example 4.
[0029] Description of reference numerals: 100-energy storage system, 110-electric energy conversion device, 200-energy storage device, 210-casing, 300-battery, 310-positive electrode plate, 311-positive electrode current collector, 312-positive electrode active layer, 330-negative electrode plate, 331-negative electrode current collector, 332-negative electrode active layer, 340-casing, 341-receiving cavity, 350-end cover assembly, 400-diaphragm, 410-base film, 420-electrolyte coating, 500-solid electrolyte particles, 510-core, 520-adhesive layer. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0031] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0032] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0033] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0034] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.
[0035] The current energy storage (i.e., energy storage) application scenarios are relatively broad, including power generation side energy storage, grid side energy storage, and power consumption side energy storage. The following uses power generation side energy storage as an example to describe the energy storage system of the embodiment of the present application in detail, which should not be understood as a limitation on the energy storage system of the embodiment of the present application.
[0036] See also Figure 1 and Figure 2The embodiment of the present application also provides an energy storage system 100, which includes: an electric energy conversion device 110 and the energy storage device 200 described in the embodiment of the present application, the electric energy conversion device 110 is electrically connected to the energy storage device 200, the electric energy conversion device 110 is used to convert other forms of energy into electric energy, and the energy storage device 200 is used to store the electric energy.
[0037] The energy storage system 100 of the embodiment of the present application can be used to generate electricity, store electrical energy, and output electrical energy when needed.
[0038] Optionally, the electric energy conversion device 110 can convert at least one other form of energy such as solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0039] Optionally, the number of the electric energy conversion devices 110 may be one or more. When there are multiple electric energy conversion devices 110, the multiple electric energy conversion devices 110 may be connected in series, in parallel, or in mixed connection, which is not specifically limited in the present application.
[0040] Optionally, the electric energy conversion device 110 may be, but is not limited to, at least one of a photovoltaic panel, a wind power generation device, a hydropower generation device, and the like.
[0041] Optionally, the number of the energy storage devices 200 may be one or more. When the number of the energy storage devices 200 is multiple, the multiple energy storage devices 200 are connected in series or in parallel, which is not specifically limited in the present application.
[0042] When working, the power conversion device 110 is used to convert other forms of energy into electrical energy and store it in the energy storage device 200. The electrical energy stored in the energy storage device 200 can be supplied to electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power / power outage. The electrical energy generated by the power conversion device 110 can also be supplied to the power grid through high-voltage cables to alleviate the power supply pressure of the power grid during peak hours.
[0043] See also Figure 3 The embodiment of the present application further provides an energy storage device 200 , which includes a box body 210 and a plurality of batteries 300 , wherein the plurality of batteries 300 are stacked and accommodated in the box body 210 .
[0044] The term "plurality" means greater than or equal to two.
[0045] It can be understood that the multiple batteries 300 of the energy storage device 200 can be connected in parallel with each other; or in series with each other; or partially in parallel and partially in series (in other words, mixed connection). This application does not make any specific limitation on the connection method of the multiple batteries 300 of the same energy storage device 200.
[0046] Optionally, the energy storage device 200 may be at least one of an energy storage box, an energy storage cabinet, an energy storage module, etc. The present application does not specifically limit the form of the energy storage device 200. The form of the energy storage device 200 of the present application is merely one of its many forms and should not be understood as a limitation on the energy storage device 200 of the present application.
[0047] It should be noted that the stacking arrangement of the multiple batteries 300 can be that the multiple batteries 300 are arranged in sequence and close to each other, or the multiple batteries 300 are arranged in sequence and spaced apart. In addition, the multiple batteries 300 can be stacked in a transverse direction (such as a horizontal direction) or a longitudinal direction (such as a gravity direction). The stacking method and stacking direction of the multiple batteries 300 can be designed according to actual conditions.
[0048] It should be noted that when the energy storage device 200 is an energy storage cabinet or an energy storage box, multiple batteries 300 can be arranged to form an energy storage module, and multiple energy storage modules are stacked and arranged and electrically connected in series, parallel or mixed connection.
[0049] It can be understood that the box body 210 has a receiving cavity (not shown), and multiple batteries 300 are received in the receiving cavity. In some embodiments, each receiving cavity receives one battery 300. In other embodiments, each receiving cavity receives multiple batteries 300.
[0050] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion batteries have been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and their application range is becoming more and more extensive.
[0051] With the development of the energy storage industry, higher requirements are placed on the life attenuation and service life of lithium-ion batteries. However, the existing lithium-ion batteries have a low cycle capacity retention rate at high temperatures and poor wide temperature and long life performance.
[0052] Battery degradation is mainly caused by the reaction of lithium ions on the surface of the negative electrode of the battery. First, during charging, ester solvents are easily reduced on the surface of the low-potential negative electrode and react with lithium, thereby consuming active lithium; secondly, the negative active layer of the negative electrode is constantly expanding and shrinking during the process of lithium extraction, causing the solid electrolyte interface membrane (SEI) on the surface of the negative active layer to be constantly pulled, exposing a new interface that continuously reacts with the electrolyte, resulting in the loss of active lithium. At high temperatures, the reaction between the surface of the negative electrode and the electrolyte is further intensified, and the interface stability of the negative electrode is further reduced, which greatly reduces the high-temperature cycle performance of the battery.
[0053] See also Figure 4 and Figure 5 The embodiment of the present application provides a battery 300 , which includes an electrolyte, a positive electrode plate 310 , a separator 400 and a negative electrode plate 330 , wherein the separator 400 is located between the positive electrode plate 310 and the negative electrode plate 330 .
[0054] It should be noted that the positive electrode sheet 310 and the negative electrode sheet 330 are at least partially immersed in the electrolyte.
[0055] It can be understood that the positive electrode sheet 310, the separator 400 and the negative electrode sheet 330 are stacked in sequence to form an electrode assembly. The electrode assembly can be, but is not limited to, a winding structure, a laminated structure, etc., which is not specifically limited in the present application.
[0056] It should be noted that the positive electrode sheet 310 and the negative electrode sheet 330 may be collectively referred to as electrode sheets. In other words, the electrode sheets include the positive electrode sheet 310 and the negative electrode sheet 330 .
[0057] See also Figure 6 Optionally, the positive electrode sheet 310 includes a positive current collector 311 and a positive active layer 312, and the positive active layer 312 is disposed on the surface of the positive current collector 311. It can be understood that the positive active layer 312 can cover one surface or two opposite surfaces of the positive current collector 311.
[0058] Optionally, the positive electrode current collector 311 may be, but is not limited to, an aluminum sheet.
[0059] Optionally, the positive electrode active layer 312 includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode thickener.
[0060] Optionally, the positive electrode active material may be, but is not limited to, lithium iron phosphate.
[0061] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0062] Optionally, the positive electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene butadiene rubber (SBR).
[0063] Optionally, in the positive electrode active layer 312, the mass fraction of the positive electrode binder ranges from 2wt% to 4wt%. Specifically, in the positive electrode active layer 312, the mass fraction of the positive electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the positive electrode binder is too small, the positive electrode active layer 312 is prone to pulverization or slag; if the mass fraction of the positive electrode binder is too large, the energy density of the positive electrode sheet 310 is reduced.
[0064] Optionally, the positive electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM), polymethacrylate (PMA), and the like.
[0065] See also Figure 7 Optionally, the negative electrode sheet 330 includes a negative electrode current collector 331 and a negative electrode active layer 332, and the negative electrode active layer 332 is disposed on the surface of the negative electrode current collector 331. It can be understood that the negative electrode active layer 332 can cover one surface or two opposite surfaces of the negative electrode current collector 331.
[0066] Optionally, the negative electrode current collector 331 may be, but is not limited to, a copper sheet.
[0067] Optionally, the negative electrode active layer 332 includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.
[0068] Optionally, the negative electrode active material may be, but is not limited to, graphite.
[0069] Optionally, the negative electrode conductive agent may be, but is not limited to, at least one of conductive carbon black (SP for short), acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.
[0070] Optionally, the negative electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, styrene-butadiene rubber, and the like.
[0071] Optionally, in the negative electrode active layer 332, the mass fraction of the negative electrode binder ranges from 2wt% to 4wt%. Specifically, in the negative electrode active layer 332, the mass fraction of the negative electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the negative electrode binder is too small, the negative electrode active layer 332 is prone to pulverization or slag; if the mass fraction of the negative electrode binder is too large, the energy density of the negative electrode plate 330 is reduced.
[0072] In the embodiments of the present application, when a numerical value range from a to b is involved, unless otherwise specified, it means that the numerical value can be any numerical value between a and b, including the endpoint numerical value a and the endpoint numerical value b.
[0073] Optionally, the negative electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC), polyacrylamide (PAM), polymethacrylate (PMA), and the like.
[0074] Please see again Figure 4 and Figure 5 Optionally, the battery 300 further includes a shell 340 and an end cover assembly 350 , wherein the shell 340 and the end cover assembly 350 enclose a receiving cavity 341 , and the receiving cavity 341 is used to receive the electrolyte, the positive electrode plate 310 , the diaphragm 400 and the negative electrode plate 330 .
[0075] Optionally, the electrolyte includes an electrolyte salt, a film-forming additive and an organic solvent. When the electrolyte is applied to the lithium-ion battery 300, the film-forming additive can be used to promote the formation of an interface film of at least one of the positive electrode sheet and the negative electrode sheet 330 and maintain the stability of the interface film.
[0076] Optionally, the electrolyte salt is a lithium salt. The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiODFP), lithium difluorobis(oxalatoborate) (LiODFB), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonate (CF3SO3Li), etc.
[0077] Optionally, in the electrolyte, the total molar concentration M of the lithium salt is in the range of 0.7mol / L≤M≤1.4mol / L. In the electrolyte, the total molar concentration M of the lithium salt may be, but is not limited to, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, etc. If the total molar concentration M of the lithium salt is too small, the concentration of free ions in the electrolyte is too small, which reduces the conductivity of the electrolyte and thus reduces the kinetic performance of the battery 300; if the total molar concentration M of the lithium salt is too large, it is easy for a part of the electrolyte salt to be undissociated, and the viscosity of the electrolyte will increase, which in turn reduces the conductivity of the electrolyte and also reduces the kinetic performance of the battery 300. When the total molar concentration M of the lithium salt in the electrolyte is in the range of 0.7 mol / L≤M≤1.4 mol / L, the electrolyte can have a higher conductivity, so that the battery 300 has better kinetic performance.
[0078] Optionally, the film-forming additive includes at least one of vinyl sulfate (DTD), vinylene carbonate (VC), vinyl carbonate (VEC), fluoroethylene carbonate (FEC), tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, adiponitrile, succinonitrile, and 1,3,6-hexanetrinitrile.
[0079] Optionally, the mass fraction of the film-forming additive ranges from 1.5% to 3%. Specifically, the mass fraction of the film-forming additive may be, but is not limited to, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc.
[0080] Optionally, the electrolyte also includes an organic solvent. The organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Cyclic carbonates have a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode plate 330, but their viscosity is relatively large. Chain carbonates have lower viscosity than cyclic carbonates, better electrochemical stability, and can improve the low-temperature performance of the electrolyte. Therefore, when a mixed solvent of cyclic carbonate and chain carbonate is used, the electrolyte can have a more suitable viscosity and low-temperature stability, and the battery 300 using the electrolyte can be better film-formed.
[0081] Optionally, the cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC for short), propylene carbonate (PC for short), etc. The dielectric constant of ethylene carbonate is much greater than that of propylene carbonate, and ethylene carbonate can better promote the formation of SEI film.
[0082] Optionally, the linear carbonate may include but is not limited to at least one of dimethyl carbonate (DMC for short), diethyl carbonate (DEC for short), ethyl methyl carbonate (EMC for short), and the like.
[0083] Optionally, in the electrolyte, the mass fraction of the organic solvent is 60wt% to 85wt%, specifically, but not limited to, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc.
[0084] Optionally, the organic solvent further comprises at least one of ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, γ-butyrolactone, and 2,2-difluoroethyl acetate.
[0085] In the related art, a layer of electrolyte coating containing solid electrolyte is coated on the surface of the battery's diaphragm to improve the battery's kinetic performance and energy efficiency (referred to as energy efficiency). However, the inorganic solid electrolyte in the related art has strong water absorption and high water content, which can easily cause hipot failure when the battery is subjected to a high voltage test (hipot test).
[0086] Adding a pre-baking device in front of the winder can improve the defect of strong water absorption of inorganic solid electrolytes. However, it brings great difficulty to the production line transformation and greatly increases the preparation cost of the diaphragm and battery.
[0087] See also Figure 8 The embodiment of the present application further provides a diaphragm 400 , which includes: a base film 410 and an electrolyte coating 420 , and the electrolyte coating 420 includes solid electrolyte particles 500 .
[0088] It should be noted that the separator 400 is used to insulate the positive electrode plate from the negative electrode plate, but the separator 400 has ion conductivity, that is, ions can pass through the separator 400.
[0089] Optionally, the base film 410 may be, but is not limited to, at least one of a polypropylene film (PP film for short), a polyethylene film (PE film for short), a ceramic base film 410 , and the like.
[0090] Optionally, the thickness of the base film 410 is 5μm to 15μm. Specifically, the thickness of the base film 410 can be but is not limited to 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 14.5μm, 15μm, etc.
[0091] Optionally, the electrolyte coating 420 further includes an adhesive, and the adhesive includes at least one of polyacrylic acid (PAA), styrene-butadiene rubber, and the like.
[0092] In a specific embodiment, the solid electrolyte particles 500, polyacrylic acid, styrene-butadiene rubber and the wetting agent are dispersed in deionized water, stirred evenly, and then evenly coated on one side of the base film 410 by micro-concave roller coating. After drying, the diaphragm 400 of the embodiment of the present application is obtained.
[0093] See also Fig. 9 The embodiment of the present application also provides a solid electrolyte particle 500, which includes a core 510 and an adhesive layer 520, wherein the adhesive layer 520 is wrapped around the surface of the core 510, and the core 510 includes an inorganic solid electrolyte. The water contact angle (i.e., water drop angle) θ of the solid electrolyte particle 500 is in the range of 95°≤θ≤115°.
[0094] It can be understood that the adhesive layer 520 is wrapped around the outer periphery of the inner core 510 to prevent the inner core 510 from being exposed.
[0095] It can be understood that the solid electrolyte particle 500 in the embodiment of the present application is a core-shell structure.
[0096] Specifically, the water contact angle θ of the solid electrolyte particle 500 may be, but is not limited to, 95°, 96°, 98°, 100°, 102°, 104°, 106°, 108°, 110°, 112°, 114°, 115°, etc. If the water contact angle θ of the solid electrolyte particle 500 is too small, the hydrophobicity of the solid electrolyte particle 500 is insufficient, and it is easy to absorb water, which may cause the battery 300 to have a hipot failure during a high voltage test; if the water contact angle θ of the solid electrolyte particle 500 is too large, the difficulty of preparing the solid electrolyte particle 500 is increased, and it may even be difficult to achieve.
[0097] Optionally, the voltage during the high voltage test ranges from 100 V to 200 V. Specifically, the voltage during the high voltage test may be, but is not limited to, 100 V, 120 V, 140 V, 160 V, 180 V, 200 V, and the like.
[0098] The solid electrolyte particle 500 of the embodiment of the present application includes a core 510 and an adhesive layer 520, wherein the adhesive layer 520 is wrapped around the surface of the core 510, and the core 510 includes an inorganic solid electrolyte. When the solid electrolyte particle 500 is applied to the diaphragm 400 of the battery 300, the adhesive layer 520 (e.g., PVDF) will be swollen by the electrolyte, and the inorganic solid electrolyte of the core 510 can increase the migration rate of ions (e.g., lithium ions), thereby improving the kinetic performance and energy efficiency of the battery 300; in addition, the water contact of the solid electrolyte particle 500 The range of the angle (i.e., the water drop angle) θ is: 95°≤θ≤115°, so that the solid electrolyte particles 500 have better hydrophobicity and thus have a lower water content. When applied to the diaphragm 400 of the battery 300, Hipot defects are less likely to occur when the battery 300 is subjected to a high-voltage test, thereby improving the preparation yield of the diaphragm 400; furthermore, the adhesive layer 520 can also play a weak bonding role with the positive electrode sheet 310 or the negative electrode sheet 330, thereby improving the bonding performance of the interface between the electrolyte coating 420 and the positive electrode sheet 310 or the negative electrode sheet 330.
[0099] In some embodiments, the water content of the solid electrolyte particles 500 is less than or equal to 1000 ppm.
[0100] Specifically, the water content of the solid electrolyte particles 500 may be, but is not limited to, less than or equal to 1000 ppm, less than or equal to 950 ppm, less than or equal to 900 ppm, less than or equal to 850 ppm, less than or equal to 800 ppm, less than or equal to 750 ppm, less than or equal to 700 ppm, less than or equal to 650 ppm, less than or equal to 600 ppm, less than or equal to 550 ppm, less than or equal to 500 ppm, less than or equal to 450 ppm, less than or equal to 400 ppm, etc.
[0101] In this embodiment, the lower the water content of the solid electrolyte particles 500 is, the better. However, if the water content of the solid electrolyte particles 500 is too low, it may be technically difficult to achieve. If the water content of the solid electrolyte particles 500 is too high, when the solid electrolyte particles 500 are applied to the diaphragm 400 of the battery 300, Hipot defects are likely to occur when the battery 300 is subjected to a high voltage test.
[0102] Furthermore, the water content of the solid electrolyte particles 500 is in the range of 500ppm to 1000ppm. This can reduce the difficulty of preparing the solid electrolyte particles 500, and at the same time, when the solid electrolyte particles 500 are applied to the battery 300, the probability of Hipot failure of the battery 300 during high voltage testing can be better reduced.
[0103] In some embodiments, the inorganic solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), etc.
[0104] Optionally, the chemical formula of lithium aluminum titanium phosphate is Li 1+x Al x Ti 2−x (PO4)3, wherein x ranges from 0.2 to 0.5, specifically, x can be but is not limited to 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.
[0105] In this embodiment, these inorganic solid electrolytes have higher ionic conductivity. When these inorganic solid electrolytes are used as the core 510 of the solid electrolyte particles 500 and applied to the diaphragm 400, the ionic conductivity of the isolation can be better improved. In addition, these inorganic solid electrolytes have higher chemical stability and are not easy to react during the charging and discharging process of the battery 300.
[0106] Optionally, the adhesive layer 520 includes a hydrophobic material. The hydrophobic material has good hydrophobicity, which can better improve the water contact angle of the solid electrolyte particles 500 and reduce the water absorption of the solid electrolyte particles 500, thereby reducing the probability of Hipot failure of the battery 300 during high voltage testing and improving the yield of the battery 300.
[0107] Optionally, the hydrophobic material includes but is not limited to polyvinylidene fluoride (PVDF). Polyvinylidene fluoride has good adhesive properties, so that when the solid electrolyte particles 500 are applied to the separator 400, they can be better bonded to the positive electrode plate 310 or the negative electrode plate 330 and the base film 410; in addition, polyvinylidene fluoride has good hydrophobicity, which can better improve the water contact angle of the solid electrolyte particles 500, thereby reducing the water content of the solid electrolyte particles 500.
[0108] It is understandable that the hydrophobic material is an adhesive, and the adhesive is wrapped on the surface of the core 510 to form an adhesive layer 520. It is understandable that the adhesive includes but is not limited to polyvinylidene fluoride (PVDF).
[0109] In some embodiments, the particle size d1 of the core 510 is in the range of 300 nm ≤ d1 ≤ 700 nm.
[0110] Specifically, the particle size d1 of the inner core 510 may be, but is not limited to, 300nm, 330nm, 350nm, 380nm, 400nm, 430nm, 450nm, 480nm, 500nm, 530nm, 550nm, 580nm, 600nm, 630nm, 650nm, 680nm, 700nm, etc.
[0111] In this embodiment, if the particle size d1 of the core 510 is too small, the cost of the core 510 will be increased. In addition, when the solid electrolyte particles 500 and the adhesive are coated on the base film 410 to form the electrolyte coating 420, the density of the solid electrolyte particles 500 in the electrolyte coating 420 is too high, which will reduce the speed of ion transmission and reduce the dynamic performance of the battery 300. If the particle size d1 of the core 510 is too large, when the solid electrolyte particles 500 are applied to the electrolyte coating 420, the thickness of the electrolyte coating 420 is difficult to control and the heat resistance of the electrolyte coating 420 will be reduced.
[0112] In some embodiments, the thickness d2 of the adhesive layer 520 is in the range of 100 nm≤d1≤400 nm.
[0113] Specifically, the thickness d2 of the adhesive layer 520 may be, but is not limited to, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 230 nm, 250 nm, 280 nm, 300 nm, 330 nm, 350 nm, 380 nm, 400 nm, etc.
[0114] In this embodiment, if the thickness d2 of the adhesive layer 520 is too small, the bonding performance of the solid electrolyte particles 500 is reduced; in addition, the adhesive layer 520 is easily unevenly distributed, thereby reducing the water contact angle of the solid electrolyte particles 500, increasing the water content of the solid electrolyte particles 500, and increasing the probability of Hipot occurring when the battery 300 is subjected to a high voltage test. If the thickness d2 of the adhesive layer 520 is too large, the thermal shrinkage rate of the diaphragm 400 will increase. The increase in the thermal shrinkage rate of the diaphragm 400 increases the probability of direct contact between the positive electrode sheet 310 and the negative electrode sheet 330, and increases the risk of short circuit of the battery 300.
[0115] Optionally, the particle size d of the solid electrolyte particles 500 is in the range of 500 nm to 1 μm.
[0116] Specifically, the particle size d of the solid electrolyte particles 500 may be, but is not limited to, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1 μm, etc.
[0117] In this embodiment, if the particle size d of the solid electrolyte particles 500 is too small, at least one of the particle size of the core 510 and the thickness of the bonding layer 520 is too small. If the particle size of the core 510 is too small, the cost of the core 510 is increased. In addition, when the solid electrolyte particles 500 and the adhesive are coated on the base film 410 to form the electrolyte coating 420, the density of the solid electrolyte particles 500 in the electrolyte coating 420 is too high, which will reduce the speed of ion transmission and reduce the dynamic performance of the battery 300. If the thickness of the bonding layer 520 is too small, the bonding performance of the solid electrolyte particles 500 is reduced. In addition, the bonding layer 520 is prone to uneven distribution, thereby reducing the water contact angle of the solid electrolyte particles 500, increasing the water content of the solid electrolyte particles 500, and increasing the probability of Hipot occurring when the battery 300 is subjected to a high voltage test. If the particle size d of the solid electrolyte particles 500 is too large, at least one of the particle size of the core 510 and the thickness of the bonding layer 520 is too large. When the particle size of the core 510 is too large, when the solid electrolyte particles 500 are applied to the electrolyte coating 420, the thickness of the electrolyte coating 420 is difficult to control and the heat resistance of the electrolyte coating 420 will be reduced. When the thickness d2 of the bonding layer 520 is too large, the thermal shrinkage rate of the diaphragm 400 will increase. The increase in the thermal shrinkage rate of the diaphragm 400 increases the probability of direct contact between the positive electrode plate 310 and the negative electrode plate 330, and increases the risk of short circuit in the battery 300.
[0118] In some embodiments, the ionic conductivity of the solid electrolyte particles 500 ranges from 1.4 mS / cm to 2.0 mS / cm.
[0119] Specifically, the ionic conductivity of the solid electrolyte particles 500 may be, but is not limited to, 1.4 mS / cm, 1.5 mS / cm, 1.6 mS / cm, 1.7 mS / cm, 1.8 mS / cm, 1.9 mS / cm, 2.0 mS / cm, etc. If the ionic conductivity of the solid electrolyte particles 500 is too small, the kinetic performance of the battery 300 is reduced; if the ionic conductivity of the solid electrolyte particles 500 is too large, it is difficult to achieve.
[0120] Optionally, the solid electrolyte particles 500 are prepared by using the core 510 and the adhesive by coaxial electrostatic spraying technology. In this embodiment, the solid electrolyte particles 500 are prepared by coaxial electrostatic spraying technology, so that the adhesive can be better wrapped on the surface of the core 510 to form an adhesive layer 520, and the adhesive layer 520 has a more uniform thickness, which can better wrap the core 510, thereby better improving the hydrophobicity of the solid electrolyte particles 500 and reducing the water absorption performance of the solid electrolyte particles 500, thereby reducing the probability of Hipot failure when the battery 300 is tested at high voltage.
[0121] "Coaxial electrostatic spray" is a technology that uses a high-voltage electrostatic field to charge and atomize liquids. The basic principle of coaxial electrostatic spray: The basic principle of coaxial electrostatic spray is to spray two immiscible fluids through a coaxial nozzle. These fluids are dispersed into tiny droplets under the action of electrostatic force and other forces in the high-voltage electrostatic field. The outer fluid and the inner fluid form a concentric circle structure in the nozzle. By adjusting parameters such as voltage, flow rate and nozzle diameter, the particle size and shape of the droplets can be controlled.
[0122] The solid electrolyte particles 500 of the embodiments of the present application can be prepared by the methods described in the following embodiments of the present application. In addition, they can also be prepared by other methods. The preparation methods of the embodiments of the present application are merely one or more preparation methods of the solid electrolyte particles 500 of the present application and should not be construed as limiting the solid electrolyte particles 500 provided in the embodiments of the present application.
[0123] In some embodiments, the range of the water contact angle θ' of the electrolyte coating 420 is: 95°≤θ'≤115°. Specifically, the water contact angle θ' of the electrolyte coating 420 can be, but is not limited to, 95°, 96°, 98°, 100°, 102°, 104°, 106°, 108°, 110°, 112°, 114°, 115°, etc. If the water contact angle θ' of the electrolyte coating 420 is too small, the hydrophobicity of the electrolyte coating 420 is insufficient, and it is easy to absorb water, which can easily cause the battery 300 to have a poor hipot during a high voltage test; if the water contact angle θ' of the electrolyte coating 420 is too large, it increases the difficulty of preparing the electrolyte coating 420, and it is even difficult to achieve.
[0124] Optionally, the water content of the electrolyte coating 420 is less than or equal to 1000ppm. Specifically, the water content of the electrolyte coating 420 may be, but is not limited to, less than or equal to 1000ppm, less than or equal to 950ppm, less than or equal to 900ppm, less than or equal to 850ppm, less than or equal to 800ppm, less than or equal to 750ppm, less than or equal to 700ppm, less than or equal to 650ppm, less than or equal to 600ppm, less than or equal to 550ppm, less than or equal to 500ppm, less than or equal to 450ppm, less than or equal to 400ppm, etc. In this embodiment, the lower the water content of the electrolyte coating 420, the better. However, if the water content of the electrolyte coating 420 is too low, it may be technically difficult to achieve; if the water content of the electrolyte coating 420 is too high, when the electrolyte coating 420 is applied to the electrolyte coating 420 of the battery 300, when the battery 300 is subjected to a high voltage test, Hipot defects are easily generated.
[0125] Optionally, the water content of the electrolyte coating 420 is less than the water content of the solid electrolyte particles 500 .
[0126] Furthermore, the water content of the electrolyte coating 420 is in the range of 500ppm to 1000ppm. This can reduce the difficulty of preparing the electrolyte coating 420, and at the same time, when the electrolyte coating 420 is applied to the battery 300, the probability of Hipot failure of the battery 300 during high voltage testing can be better reduced.
[0127] Optionally, the ionic conductivity of the electrolyte coating 420 is less than the ionic conductivity of the solid electrolyte particles 500 .
[0128] Optionally, the ionic conductivity of the electrolyte coating 420 is in the range of 1.3 mS / cm to 2.0 mS / cm.
[0129] Specifically, the ionic conductivity of the electrolyte coating 420 may be, but is not limited to, 1.3 mS / cm, 1.4 mS / cm, 1.5 mS / cm, 1.6 mS / cm, 1.7 mS / cm, 1.8 mS / cm, 1.9 mS / cm, 2.0 mS / cm, etc. If the ionic conductivity of the electrolyte coating 420 is too small, the kinetic performance of the battery 300 is reduced; if the ionic conductivity of the electrolyte coating 420 is too large, it is difficult to achieve.
[0130] In some embodiments, the electrolyte coating 420 has a thickness ranging from 0.5 μm to 3 μm.
[0131] Specifically, the thickness of the electrolyte coating 420 may be, but is not limited to, 0.5 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, etc.
[0132] In this embodiment, the inorganic solid electrolyte can improve the heat resistance of the diaphragm 400. When the thickness of the electrolyte coating 420 is too thin, the proportion of the stepless solid electrolyte in the diaphragm 400 is too small, which is not conducive to improving the heat resistance of the diaphragm 400; when the thickness of the electrolyte coating 420 is too thick, when the size of the battery 300 is constant, the volume of the positive electrode plate 310 and the negative electrode plate 330 is reduced, and the energy density of the battery 300 is reduced; in addition, the cost of the diaphragm 400 is increased; furthermore, this makes the path for ions to pass through the diaphragm 400 too long, reducing the kinetic performance of the battery 300.
[0133] Optionally, the thermal shrinkage rate of the diaphragm 400 after being heated at 130° C. for 30 minutes is less than or equal to 5%.
[0134] Specifically, the thermal shrinkage rate of the diaphragm 400 after heating at 130°C for 30 minutes may be, but is not limited to, less than or equal to 5%, less than or equal to 4.8%, less than or equal to 4.5%, less than or equal to 4.3%, less than or equal to 4%, less than or equal to 3.8%, less than or equal to 3.5%, less than or equal to 3.3%, less than or equal to 3%, less than or equal to 2.8%, less than or equal to 2.5%, less than or equal to 2.3%, less than or equal to 2%, etc.
[0135] In this embodiment, the thermal shrinkage rate of the diaphragm 400 after heating at 130°C for 30 minutes is too small, and the thickness of the adhesive layer 520 may be too thin, and the content of the adhesive is too little, which reduces the bonding performance of the electrolyte coating 420; in addition, the adhesive layer 520 is too thin and is prone to uneven distribution, thereby reducing the water contact angle of the electrolyte coating 420, increasing the water content of the electrolyte coating 420, and increasing the probability of Hipot when the battery 300 is tested for high voltage. If the thermal shrinkage rate of the diaphragm 400 after heating at 130°C for 30 minutes is too large, when the diaphragm 400 is applied to the battery 300, the thermal shrinkage rate of the electrolyte coating 420 is increased, the probability of direct contact between the positive electrode plate 310 and the negative electrode plate 330 is increased, and the risk of short circuit of the battery 300 is increased.
[0136] Furthermore, the thermal shrinkage of the separator 400 after heating at 130°C for 30 minutes ranges from 2.5% to 5%. This can better reduce the probability of Hipot occurring in the battery 300 using the electrolyte coating 420 during high voltage testing, and can also make the separator 400 have a lower thermal shrinkage, reduce the probability of direct contact between the positive electrode sheet 310 and the negative electrode sheet 330, and reduce the risk of short circuit in the battery 300.
[0137] In some embodiments, the electrolyte coating 420 is located between the base film 410 and the positive electrode plate 310 .
[0138] It can be understood that when the separator 400 is applied to the battery 300 , the electrolyte coating 420 is disposed facing the positive electrode plate 310 . In other words, the positive electrode plate 310 is closer to the electrolyte coating 420 than the negative electrode plate 330 .
[0139] It can be understood that the positive electrode plate 310, the electrolyte coating 420, the base film 410, and the negative electrode plate 330 are stacked in sequence.
[0140] When the electrolyte coating 420 is located between the base film 410 and the negative electrode plate 330, when the battery 300 is formed, the core 510 (such as LATP) of the solid electrolyte particles 500 in the electrolyte coating 420 reacts with the negative electrode plate 330 to form a protective film, thereby reducing the initial efficiency of the battery 300. In this embodiment, the electrolyte coating 420 is located between the base film 410 and the positive electrode plate 310.
[0141] See also Fig.10 The present application also provides a method for preparing a solid electrolyte particle 500, the method comprising: S601, providing a core 510 dispersion and an adhesive solution; and In some embodiments, the inorganic solid electrolyte is lithium aluminum titanium phosphate and the binder is polyvinylidene fluoride.
[0142] Optionally, providing a core 510 dispersion includes: lithium aluminum titanium phosphate is dispersed in water, 1 wt % of polyacrylic acid is added as a dispersant, and stirring is performed for 0.5 h to 2 h (for example, 0.5 h, 1 h, 1.5 h, 2 h, etc.), and the stirring speed can be 1600 r / min to 2000 r / min (for example, 1600 r / min, 1700 r / min, 1800 r / min, 1900 r / min, 2000 r / min, etc.) to obtain a core 510 dispersion.
[0143] Optionally, in the dispersion of the core 510, the mass fraction of the core 510 ranges from 10 wt % to 40 wt %. Specifically, the mass fraction of the core 510 in the dispersion of the core 510 may be, but is not limited to, 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, etc.
[0144] Optionally, providing the adhesive solution includes: dissolving polyvinylidene fluoride in dimethylacetamide (DMA or DMAc for short) solution, stirring for 0.5h to 2h (for example, 0.5h, 1h, 1.5h, 2h, etc.), and the stirring speed can be 800r / min to 1200r / min (for example, 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min, etc.), to form a polyvinylidene fluoride solution with a mass concentration of 8% to 12% (for example, 8%, 9%, 10%, 11%, 12%, etc.).
[0145] For descriptions of other aspects of the core 510 and the adhesive, please refer to the descriptions of the corresponding parts of the above embodiments, which will not be repeated here.
[0146] S602, coaxially electrostatically spraying the inner core 510 dispersion and the adhesive solution so that the binder in the adhesive solution forms an adhesive layer 520 to obtain the solid electrolyte particle 500; wherein the solid electrolyte particle 500 includes an inner core 510 and an adhesive layer 520, the adhesive layer 520 is wrapped around the surface of the inner core 510, the inner core 510 includes an inorganic solid electrolyte, and the water contact angle θ of the solid electrolyte particle 500 is in the range of 95°≤θ≤115°.
[0147] Optionally, the core 510 dispersion is loaded into one syringe (e.g., 10 ml) of a coaxial electrostatic spray device, and the binder solution is loaded into another syringe (e.g., 10 ml) of the coaxial electrostatic spray device. Coaxial electrostatic spraying is performed at a voltage of 1.2 kV to 1.8 kV to obtain solid electrolyte particles 500.
[0148] Specifically, the voltage of the coaxial electrostatic spray may be, but is not limited to, 1.2 kV, 1.3 kV, 1.4 kV, 1.5 kV, 1.6 kV, 1.7 kV, 1.8 kV, etc. If the voltage of the coaxial electrostatic spray is too low, the particle size of the solid electrolyte particles 500 obtained is too large, and the electrolyte coating 420 is too thick and does not meet the requirements; if the voltage of the coaxial electrostatic spray is too high, the particle size of the solid electrolyte particles 500 obtained is too small, making the particle size distribution of the solid electrolyte particles 500 uneven, affecting the uniformity of the thickness of the electrolyte coating 420.
[0149] Optionally, the injection speed of the core 510 dispersion is in the range of 0.2 ml / h to 0.5 ml / h. Specifically, the injection speed of the core 510 dispersion can be, but is not limited to, 0.2 ml / h, 0.3 ml / h, 0.4 ml / h, 0.5 ml / h, etc. If the injection speed of the core 510 dispersion is too slow, the particle size of the core 510 of the prepared solid electrolyte particle 500 is too small, and the thickness of the bonding layer 520 is too thick, which will increase the thermal shrinkage rate of the diaphragm 400. The increased thermal shrinkage rate of the diaphragm 400 increases the probability of direct contact between the positive electrode plate 310 and the negative electrode plate 330, and increases the risk of short circuit in the battery 300; if the injection speed of the core 510 dispersion is too fast, the particle size of the core 510 of the prepared solid electrolyte particle 500 is too large, and the thickness of the bonding layer 520 is too thin, which reduces the bonding performance of the solid electrolyte particle 500; in addition, the bonding layer 520 is prone to uneven distribution, thereby reducing the water contact angle of the solid electrolyte particle 500, increasing the water content of the solid electrolyte particle 500, and increasing the probability of Hipot occurring when the battery 300 is subjected to high voltage testing.
[0150] Optionally, the injection speed of the binder solution ranges from 0.6 ml / h to 1.0 ml / h. Specifically, the injection speed of the binder solution may be, but is not limited to, 0.6 ml / h, 0.7 ml / h, 0.8 ml / h, 0.9 ml / h, 1.0 ml / h, etc. If the injection speed of the adhesive solution is too slow, the particle size of the core 510 of the prepared solid electrolyte particle 500 is too large, and the thickness of the adhesive layer 520 is too thin, which reduces the bonding performance of the solid electrolyte particle 500; in addition, the adhesive layer 520 is prone to uneven distribution, thereby reducing the water contact angle of the solid electrolyte particle 500, increasing the water content of the solid electrolyte particle 500, and increasing the probability of Hipot occurring when the battery 300 is subjected to a high voltage test; if the injection speed of the adhesive solution is too fast, the particle size of the core 510 of the prepared solid electrolyte particle 500 is too small, and the thickness of the adhesive layer 520 is too thick, which will increase the thermal shrinkage rate of the diaphragm 400. The increase in the thermal shrinkage rate of the diaphragm 400 increases the probability of direct contact between the positive electrode plate 310 and the negative electrode plate 330, and increases the risk of short circuit in the battery 300.
[0151] Optionally, the receiving distance ranges from 5 cm to 15 cm. Specifically, the receiving distance may be, but is not limited to, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc. If the receiving distance is too short, the voltage will not be able to break the droplets into smaller pieces, the particle size of the solid electrolyte particles 500 obtained will be too large, and the electrolyte coating 420 will be too thick and will not meet the requirements; if the receiving distance is too long, a larger voltage needs to be applied. In addition, the particle size of the solid electrolyte particles 500 obtained will be too small, making the particle size distribution of the solid electrolyte particles 500 uneven, affecting the uniformity of the thickness of the electrolyte coating 420.
[0152] "Receiving distance" refers to the distance from the coaxial pillow of the coaxial electrostatic spray device to the receiving liquid.
[0153] The solid electrolyte particles 500 of the embodiment of the present application are prepared by coaxial electrostatic spraying technology, so that the adhesive can be better wrapped on the surface of the inner core 510 to form an adhesive layer 520, the thickness of the adhesive layer 520 is more uniform, and the adhesive layer 520 wraps the inner core 510 more uniformly, thereby better improving the hydrophobicity of the solid electrolyte particles 500, improving the water contact angle of the solid electrolyte particles 500, and better reducing the water content of the solid electrolyte particles 500. When the solid electrolyte particles 500 are applied to the diaphragm 400 of the battery 300, when the battery 300 is subjected to a high-voltage test, Hipot defects are less likely to occur, thereby improving the preparation yield of the diaphragm 400.
[0154] The solid electrolyte particles 500, the separator 400 and the battery 300 of the present application are further described below through specific embodiments.
[0155] Example 1 to Example 13 The preparation method of the battery 300 of each embodiment and comparative example includes: (1) Preparation of positive electrode sheet 310: The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (positive electrode conductive agent, Super-P), and solid electrolyte particles 500 (positive electrode binder, PVDF) are dispersed in N-methylpyrrolidone (NMP) solvent according to a preset mass ratio, mixed evenly and prepared into a positive electrode slurry with a solid content of 60%; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector 311 aluminum foil with a thickness of 10 μm, and the coating weight of the positive electrode slurry is 300 mg / 1540.25 mm2; after drying, cold pressing, slitting, and cutting, the positive electrode slurry is solidified to form a positive electrode active layer 312, thereby obtaining a positive electrode sheet 310, wherein the thickness of a single side of the positive electrode active layer 312 is 100 μm; (2) Preparation of negative electrode sheet 330: Graphite (negative electrode active material), sodium carboxymethyl cellulose (negative electrode thickener, abbreviated as CMC), styrene-butadiene rubber emulsion (negative electrode binder SBR), and asphalt are dispersed in deionized water according to a preset mass ratio and prepared into a negative electrode slurry with a solid content of 50%. The negative electrode slurry is evenly coated on a negative electrode current collector 331 copper foil with a thickness of 6 μm. The coating weight of the negative electrode slurry is 144 mg / 1540.25 mm². After drying, cold pressing, slitting, and cutting, the negative electrode slurry is solidified to form a negative electrode active layer 332, thereby obtaining a negative electrode sheet 330, wherein the thickness of a single side of the negative electrode active layer 332 is 70 μm. (3) Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1 ppm, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1 to obtain a mixed solvent, and then dry electrolyte salt lithium hexafluorophosphate is dissolved in the mixed solvent and stirred until completely dissolved and uniformly dissolved, and 1% vinylene carbonate (VC) and 2% fluoroethylene carbonate (FEC) are added and stirred uniformly to obtain an electrolyte, wherein the molar concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L; (4) Preparation of diaphragm 400: i) LATP dispersion preparation: Disperse LATP particles of a preset particle size evenly into water, add 1 wt% polyacrylic acid as a dispersant, stir at 1800 r / min for 1 h, and then load into a 10 ml syringe of a coaxial electrostatic spray device for use; ii) PVDF solution preparation: Dissolve a preset weight of PVDF powder in 90 ml of DMAc solvent, stir at 1000 r / min for 1 h, and then load into another syringe of a 10 ml coaxial electrostatic spray device for use; iii) Coaxial electrostatic spray: Inject the LATP dispersion at a preset injection speed, inject the PVDF solution at a preset injection speed, perform coaxial electrostatic spraying at a voltage of 1.5 kV and a receiving distance of 10 cm, and the spray liquid falls into the coaxial electrostatic spray device. In the prepared aqueous solution collection tank, the PVDF solution can undergo phase separation after contacting water to form stable PVDF-coated LATP solid electrolyte particles 500; wherein, the material and particle size of the core 510 of the solid electrolyte particles 500 of each embodiment, and the material and thickness of the adhesive layer 520 are shown in Table 1 below, and the thickness of the adhesive layer 520 can be adjusted by the injection rate of the PVDF solution; iv) 5 kg of solid electrolyte particles 500, 500 g of PAA (polyacrylic acid), 100 g of SBR (styrene-butadiene rubber), and 5 g of wetting agent are added to 15 kg of deionized water, stirred evenly, and then evenly coated on one side of a polyethylene base film 410 with a thickness of 7 μm by micro-concave roller coating, and dried to obtain a diaphragm 400, wherein the thickness of the electrolyte coating 420 is 2 μm; and (5) Assembly of battery 300: The positive electrode sheet 310, the separator 400, and the negative electrode sheet 330 are stacked in sequence to form an electrode assembly, and the electrolyte coating 420 of the separator 400 faces the positive electrode sheet 310. The electrode assembly is wound to obtain a bare cell. After welding the tabs, the bare cell is assembled into an outer package. After injecting electrolyte, the cell is vacuum packaged, allowed to stand, formed, shaped, and capacity tested, and finally a soft-pack battery 300 is prepared.
[0156] Comparative Example 1 The difference between this comparative example and Example 3 is that the electrolyte coating 420 of this comparative example is an alumina ceramic coating (referred to as CCS coating), and the thickness of the alumina ceramic coating is 2 μm.
[0157] Comparative Example 2 The difference between this comparative example and Example 3 is that the inorganic solid electrolyte in the electrolyte coating 420 of this comparative example is lithium titanium aluminum phosphate, without PVDF coating, the particle size of the lithium titanium aluminum phosphate is 500nm, and the thickness of the electrolyte coating 420 is 2μm.
[0158] Comparative Example 3 The difference between this comparative example and Example 3 is that in the electrolyte coating 420 of this comparative example, lithium titanium aluminum phosphate is directly mixed with PVDF of equal mass to that of Example 1 (ie, non-core-shell structure), the particle size of lithium titanium aluminum phosphate is 500nm, and the thickness of the electrolyte coating 420 is 2μm.
[0159] Comparative Example 4 The difference between this comparative example and Example 3 is that when the battery 300 is assembled, the electrolyte coating 420 of the separator 400 faces the negative electrode plate 330 .
[0160] Performance tests were performed on the separators 400 and the batteries 300 of the embodiments and comparative examples.
[0161] (1) The particle size d1 of the core 510 is measured using a laser particle size analyzer; the thickness d2 of the adhesive layer 520 is measured using a transmission electron microscope (TEM).
[0162] (2) Water contact angle θ of the separator 400: measured according to GB / T 30693-2014.
[0163] (3) Water content of diaphragm 400: Use Karl Fischer tester to measure according to the following steps: 1) Turn on the Karl Fischer moisture meter and add appropriate amount of Karl Fischer reagent to the titration cell; 2) Turn on the nitrogen cylinder or generator and heat to 130°C; 3) Click Start and wait for the instrument to reach electrolytic equilibrium; 4) When measuring, weigh 1g of diaphragm 400 sample into the sample injection bottle, place it on the heating furnace module, click Start measurement and record the measurement results.
[0164] (4) Thermal shrinkage of diaphragm 400: The sample was cut into strips of 500 mm × 100 mm and placed in an oven at 130°C for 30 min. After baking, the dimensional changes before and after were measured and the shrinkage ratio was calculated.
[0165] (5) Adhesion strength of the diaphragm 400 to the positive electrode sheet 310 after dry pressing: The stacked diaphragm 400 and the positive electrode sheet 310 were cut into strips of 100×100 cm, with Teflon pads on the upper and lower sides. After hot pressing in a hot press, the peel strength of the diaphragm 400 and the positive electrode sheet 310 was tested and recorded with reference to GB8808.
[0166] (6) Ionic conductivity: tested by electrochemical impedance spectroscopy (EIS test). 1) Diaphragm 400: cut into 26 mm diameter discs, the reaction area is a 16 mm diameter circle; 2) Electrolyte: ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) with a volume ratio of 1:1:1 as a mixed solvent, LiPF6 as an electrolyte, and a LiPF6 concentration of 1 mol / L electrolyte; 3) Test conditions: 20 kg, immersion time 20 min; 4) EIS test frequency: 100 kHz~1000 Hz (the frequency limit range of the EIS module is 100 k~0.01 Hz).
[0167] (7) Energy efficiency at 5°C (abbreviated as energy efficiency): tested in accordance with GB / T 36276-2023.
[0168] (8) Energy efficiency at 25°C (abbreviated as energy efficiency): tested in accordance with GB / T 36276-2023.
[0169] (9) Initial efficiency at 25°C (referred to as initial efficiency): tested in accordance with GB / T 36276-2023.
[0170] The performance parameters of the separator 400 and the battery 300 of each embodiment and comparative example are shown in Table 2 below.
[0171]
[0172] Fig.11 is a transmission electron microscope image of the solid electrolyte particle 500 prepared in Example 4. Fig.11 It can be seen that a layer of adhesive layer 520 is evenly wrapped on the surface of the inner core 510 .
[0173] From the test results of Examples 1 to 5, it can be seen that as the particle size of the core 510 increases, the water contact angle θ of the diaphragm 400 (the electrolyte coating 420 side, i.e., the water contact angle of the electrolyte coating 420) decreases slightly, the water content of the diaphragm 400 gradually increases, the thermal shrinkage rate of the diaphragm 400 gradually decreases, and the adhesion of the diaphragm 400 to the positive electrode plate 310 after dry pressing first gradually increases and then gradually decreases. In addition, as the particle size of the core 510 increases, the ionic conductivity of the electrolyte coating 420 gradually increases, the first efficiency of the battery 300 at 25°C remains almost unchanged, and the energy efficiency of the battery 300 at 5°C and the energy efficiency at 25°C increase slightly, but the effect is very small.
[0174] From the test results of Examples 3, 6 to 11, it can be seen that as the thickness of the adhesive layer 520 increases, the water contact angle θ of the diaphragm 400 (the electrolyte coating 420 side, i.e., the water contact angle of the electrolyte coating 420) gradually increases, the water content of the diaphragm 400 gradually decreases, the thermal shrinkage rate of the diaphragm 400 gradually decreases, and the adhesive force of the diaphragm 400 to the positive electrode plate 310 after dry pressing gradually increases. As the thickness of the adhesive layer 520 increases, the ionic conductivity of the electrolyte coating 420 gradually decreases, the first efficiency of the battery 300 at 25°C remains almost unchanged, and the energy efficiency of the battery 300 at 5°C and 25°C is slightly reduced, but the impact is small.
[0175] From the test results of Example 3, Example 12 to Example 13, it can be seen that the use of lithium titanium aluminum phosphate particles, lithium lanthanum zirconium oxide particles or lithium lanthanum titanium oxide particles as the core 510 of the solid electrolyte particles 500 can make the prepared diaphragm 400 have a higher water contact angle, lower water content, lower thermal shrinkage, and higher adhesion of the diaphragm 400 to the positive electrode plate 310 after dry pressing. The battery 300 has a higher first efficiency at 25°C, and the battery 300 has a higher energy efficiency at 5°C and 25°C. In addition, the ionic conductivity of the electrolyte coating 420 prepared by using lithium titanium aluminum phosphate particles, lithium lanthanum zirconium oxide particles or lithium lanthanum titanium oxide particles as the core 510 of the solid electrolyte particles 500 is not much different.
[0176] It can be seen from the test results of Example 3 and Comparative Example 1 that, compared with the electrolyte coating 420 made of alumina ceramic particles in Comparative Example 1, the solid electrolyte particles 500 of the present application as the electrolyte coating 420 have a better water contact angle, and the diaphragm 400 has a lower water content, thereby greatly reducing the probability of hipot failure in the battery 300 during high voltage testing. In addition, the thermal shrinkage rate of the diaphragm 400 has increased slightly, but the increase is small. The first efficiency of the battery 300 at 25°C is slightly reduced, but the energy efficiency of the battery 300 at 5°C and 25°C are both increased. Furthermore, compared with the electrolyte coating 420 made of alumina ceramic particles in Comparative Example 1, the electrolyte coating 420 made of the solid electrolyte particles 500 of the present application has a higher ionic conductivity, so that the battery 300 can have higher dynamic performance.
[0177] It can be seen from the test results of Example 3 and Comparative Example 2 that compared with the diaphragm 400 made of lithium aluminum titanium phosphate particles without adhesive layer 520 coating in Comparative Example 2, the diaphragm 400 made of adhesive layer 520 coating in Example 3 of the present application has a higher water contact angle and a lower water content, thereby greatly reducing the probability of hipot failure of the battery 300 during high voltage testing. In addition, the thermal shrinkage rate of the diaphragm 400 increased slightly, but the increase was small; the ionic conductivity of the electrolyte coating 420 also increased slightly; the first efficiency of the battery 300 at 25°C, the energy efficiency of the battery 300 at 5°C, and the energy efficiency of the battery 300 at 25°C did not change much.
[0178] It can be seen from the test results of Example 3 and Comparative Example 3 that, compared with the case where the material of the adhesive layer 520 is directly mixed with the core 510 in Comparative Example 3, the diaphragm 400 made of the core-shell structured solid electrolyte particles 500 of Example 3 has a higher water contact angle, and the diaphragm 400 has a lower water content, so that the probability of hipot failure of the battery 300 during high voltage testing is greatly reduced; the diaphragm 400 has a lower thermal shrinkage rate, and the diaphragm 400 has a higher adhesion to the positive electrode plate 310 dry pressing. However, the ionic conductivity of the electrolyte coating 420 is almost unchanged, and the first efficiency of the battery 300 at 25°C does not change much, but the energy efficiency of the battery 300 at 5°C and the energy efficiency at 25°C are increased.
[0179] It can be seen from the test results of Example 3 and Comparative Example 4 that, compared with the solution in which the electrolyte coating 420 of the diaphragm 400 faces the negative electrode plate 330 in Comparative Example 4, the solution in which the electrolyte coating 420 of the diaphragm 400 of Example 3 of the present application faces the positive electrode plate 310 can make the battery 300 have a higher first efficiency. This is because when the electrolyte coating 420 faces the negative electrode plate 330 (Comparative Example 4), during the formation process of the battery 300, LATP will react with the negative electrode plate 330 to form a protective film, thereby reducing the first efficiency of the battery 300.
[0180] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0181] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A solid electrolyte particle, characterized in that: The solid electrolyte particle comprises a core and an adhesive layer, wherein the adhesive layer is wrapped around the surface of the core, the core comprises an inorganic solid electrolyte, and the water contact angle θ of the solid electrolyte particle is in the range of 95°≤θ≤115°.
2. The solid electrolyte particle according to claim 1, characterized in that The water content of the solid electrolyte particles is less than or equal to 1000 ppm.
3. The solid electrolyte particle according to claim 1, characterized in that: The inorganic solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum titanium oxide; and the adhesive layer includes polyvinylidene fluoride.
4. The solid electrolyte particle according to claim 1, characterized in that: The particle size d1 of the inner core is in the range of 300nm≤d1≤700nm.
5. The solid electrolyte particle according to claim 1, characterized in that: The thickness d2 of the adhesive layer is in the range of 100 nm≤d1≤400 nm.
6. The solid electrolyte particle according to claim 1, characterized in that The solid electrolyte particles have an ionic conductivity ranging from 1.4 mS / cm to 2.0 mS / cm.
7. A method for preparing solid electrolyte particles, characterized in that: The preparation method comprises: providing a core dispersion and a binder solution; and Coaxially electrostatically spraying the core dispersion and the binder solution so that the binder in the binder solution forms a bonding layer to obtain the solid electrolyte particles; The solid electrolyte particles include a core and an adhesive layer, the adhesive layer is wrapped around the surface of the core, the core includes an inorganic solid electrolyte, and the water contact angle θ of the solid electrolyte particles is in the range of 95°≤θ≤115°.
8. A diaphragm, characterized in that: The diaphragm comprises: basement membrane; and An electrolyte coating, comprising the solid electrolyte particles according to any one of claims 1 to 7.
9. The diaphragm according to claim 8, characterized in that The thickness of the electrolyte coating ranges from 0.5 μm to 3 μm.
10. The diaphragm according to claim 8, characterized in that The thermal shrinkage rate of the diaphragm after being heated at 130° C. for 30 minutes is less than or equal to 5%.
11. A battery, characterized in that: include: An electrolyte, a positive electrode sheet, a separator according to any one of claims 8 to 10, and a negative electrode sheet, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.
12. The battery according to claim 11, characterized in that The electrolyte coating is located between the base film and the positive electrode plate.
13. An energy storage device, characterized in that: include: Box; as well as A plurality of batteries according to claim 11 or 12, wherein the plurality of batteries are housed in the casing.
Citation Information
Patent Citations
Separator having porous coating layer and electrochemical device containing the same
CN101861667A
Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof
CN112701345A
Method for improving storage stability of solid electrolyte material, material and application
CN114421023A
Composite solid electrolyte particle and preparation method and application thereof
CN115799622A
Separator, battery and electric device
WO2024187294A1